Corruption Eradication Community Movement as A Preventive Effort to Fight the Corruption of Village Funds: Gerakan Masyarakat Perangi Korupsi dalam Upaya Pencegahan Korupsi Dana Desa - Badaruddin, Sukri; Asriadi, Muhammad; Fikri Muhkam, Mirwan; Ahyadi, Nadila; Alfina; Nurfajria (QISTHOSIA : Jurnal Syariah dan Hukum, 2024)
This article discusses public unrest due to corruption giving birth to an association called the Community Movement to Fight Corruption (GMPK). GMPK in general is expected to have great potential in eradicating corruption in Indonesia by actively involving various parties and providing moral pressure to corrupt actors and policymakers to act decisively and fairly in handling corruption cases. Meanwhile, GMPK in particular is expected to play an active role in eradicating corruption and building better governance in the management of public resources in Buton Regency. This study aims to find out the role of the Community Movement to Fight Corruption in Buton Regency in efforts to prevent corruption in Buton Regency. The research method uses a descriptive type of research, with more descriptive nature from the results of interviews and documentation studies. The data obtained will be analyzed qualitatively. The analysis method is carried out during data collection and after completing data collection in a certain period. To process the data, the following methods were used: (1) data reduction, (2) data presentation, (3) conclusion drawn. As a result of the research, the implication of GMPK to the people of Buton Regency, namely as a connector of community aspirations, is required to provide the best through daily activities in preventing corruption, namely in preventive efforts (prevention) and preemptive efforts (deterrence) of corruption crimes, especially in the use of village funds. And GMPK's real efforts in preventing corruption of village funds are carried out through programs designed both long-term, short-term and medium-term programs. And the program includes conducting research to find corruption vulnerabilities in various agencies, especially in the village, in the management of village funds by looking at potential causes of corruption that can be seen from all aspects such as the use of village funds in Buton whether it is on target or not, as well as carrying out seminars and Anti-Corruption Education workshops that present all Village Heads within the scope of Buton Regency.